Clinical Features, Neuropathology, and Surgical Outcome in Patients with Refractory Epilepsy and Brain Somatic Variants in the SLC35A2 Gene - Barba, Carmen; Blümcke, Ingmar; Winawer, Melodie R.; Hartlieb, Till; Kang, Hoon Chul; Grisotto, Laura; Chipaux, Mathilde; Bien, Christian G.; Heřmanovská, Barbora; Porter, Brenda E.; Lidov, Hart G.W.; Cetica, Valentina; et al. (Neurology, 2023)
Background and ObjectivesThe SLC35A2 gene, located at chromosome Xp11.23, encodes for a uridine diphosphate-galactose transporter. We describe clinical, genetic, neuroimaging, EEG, and histopathologic findings and assess possible predictors of postoperative seizure and cognitive outcome in 47 patients with refractory epilepsy and brain somatic SLC35A2 gene variants.MethodsThis is a retrospective multicenter study where we performed a descriptive analysis and classical hypothesis testing. We included the variables of interest significantly associated with the outcomes in the generalized linear models.ResultsTwo main phenotypes were associated with brain somatic SLC35A2 variants: (1) early epileptic encephalopathy (EE, 39 patients) with epileptic spasms as the predominant seizure type and moderate to severe intellectual disability and (2) drug-resistant focal epilepsy (DR-FE, 8 patients) associated with normal/borderline cognitive function and specific neuropsychological deficits. Brain MRI was abnormal in all patients with EE and in 50% of those with DR-FE. Histopathology review identified mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy in 44/47 patients and was inconclusive in 3. The 47 patients harbored 42 distinct mosaic SLC35A2 variants, including 14 (33.3%) missense, 13 (30.9%) frameshift, 10 (23.8%) nonsense, 4 (9.5%) in-frame deletions/duplications, and 1 (2.4%) splicing variant. Variant allele frequencies (VAFs) ranged from 1.4% to 52.6% (mean VAF: 17.3 ± 13.5). At last follow-up (35.5 ± 21.5 months), 30 patients (63.8%) were in Engel Class I, of which 26 (55.3%) were in Class IA. Cognitive performances remained unchanged in most patients after surgery. Regression analyses showed that the probability of achieving both Engel Class IA and Class I outcomes, adjusted by age at seizure onset, was lower when the duration of epilepsy increased and higher when postoperative EEG was normal or improved. Lower brain VAF was associated with improved postoperative cognitive outcome in the analysis of associations, but this finding was not confirmed in regression analyses.DiscussionBrain somatic SLC35A2 gene variants are associated with 2 main clinical phenotypes, EE and DR-FE, and a histopathologic diagnosis of MOGHE. Additional studies will be needed to delineate any possible correlation between specific genetic variants, mutational load in the epileptogenic tissue, and surgical outcomes.
CRIS-Team Scopus Importer:2023-02-10